AVANT-GARDE PROSE THROUGH NARRATOLOGY CATEGORIES (NOVEL “INTELLECTUAL” BY L. SKRYPNYK) - Kaplenko О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of the article analyses the novel “Intellectual” by Leonid Skrypnyk (1929) through the categories of narratology. The logic moves from dichotomy “demonstration” / “narration” to the categories connected with the author’s narrative strategy. The basic category of “voice” in the variant by L. Skrypnyk is manifested in two guises – that of the director and that of the commentator. It gives the opportunity to state that the novel has a specific “scenic” style of the narration.